The cultural influence of the noken system on political participation in Papua - Antonita Asriani Lensru (Department of Government Science, 2025)
The noken system is a unique cultural tradition in Papua that plays a significant role in organizing and facilitating political participation. This study aims to explore the cultural influence of the noken system on political engagement in Papua. Using a qualitative approach, data were collected through in-depth interviews and participatory observation in several regions. The findings reveal that the noken system functions not only as a symbol of social solidarity but also as a consensus-based democratic mechanism that enhances political awareness and citizen involvement. Communities that practice the noken system tend to be more politically active and exhibit greater trust in electoral processes. However, this study also highlights ongoing debates about the compatibility of the noken system with modern democratic principles and human rights, including concerns over potential vote manipulation and limited individual voting freedom. The research contributes theoretically to the understanding of consensus democracy and indigenous political systems, encouraging further discussion on democratic pluralism in local contexts. Thus, the noken system holds a strategic role in strengthening culturally grounded democracy in Papua.